A(z)-Application of Ananlytic function Jordan’s Lemma - Islamov Y; Amirov Z (Zien Journals, 2022)
This article dedicated to notion of A(z)-analytic function and Jordan’s lemma. Jordan’s lemma is proved for A(z)-analytic function
Keywords: analytic function; antianalytic function; Jordan’s lemma.